Individual dietary diversity score dan kejadian stunted pada anak prasekolah di Kota Padang - Purnakarya, Idral; Ramayanti, Sri; Sari, Desy Purnama (Jurnal Gizi Klinik Indonesia, 2024)
Individual dietary diversity score and stunted in preschool children in Padang Background: Stunting is a disorder of growth and development in children due to chronic malnutrition and recurrent infections, characterized by substandard length and height.Objective: The study assesses the relationship between individual dietary diversity scores and stunting in preschool children in Padang.Methods: The study used a cross-sectional design. The sample of this study was 267 preschool children aged 3-5 years in Padang who were taken by multi-stage random sampling. Data was collected through child height measurements and individual dietary diversity score (IDDS) for food grouping measured by a 24-hour dietary recall. The data was analyzed using the Chi-Square test.Results: The results showed that 9.7% of preschool children were stunted, and 41.6% of preschool children had lower dietary diversity. The results of the study found was not significantly relationship between individual dietary diversity score and the incidence of stunting in pre-school children in Padang (p-value>0.05).Conclusions: Preschool children with IDDS secure to have a lower risk of stunting. Through a comprehensive approach that prioritizes improving dietary diversity, it is expected to be a key strategy in efforts to reduce stunting in Padang City.